Program Makan Bergizi Gratis (MBG): Antara Legacy Project dan Solusi Stunting - Aprillia, Nur Putri; Azzahra, Mutiara Umy Dwi (Journal of Information Systems and Management (JISMA), 2025)
The Free Nutritious Meals Program (MBG) is one of the government's main initiatives designed to address stunting and improve the nutritional quality of children in Indonesia. The purpose of this study is to examine the implementation of the MBG Program from the perspectives of management, fund distribution, and impact. The method used is qualitative with a literature study method through analysis of supporting data and critical evaluation related to the program's implementation. The results of the study show that the MBG not only functions as a program to address stunting but also as a legacy project with strong political implications. The main challenges faced include the lack of kitchen hygiene standards, the possibility of budget waste, and unpreparedness in implementation. The benefits of this study provide insight for decision makers in formulating improvement measures. This program must be managed openly and responsibly. The implications of the MBG's failure could risk undermining public trust and disrupting efforts to address stunting. There needs to be a temporary suspension, improvements in management, and strengthening of the digital system so that the program can run effectively and on target.